Preliminary Lessons Learned from the “Native Navigators and the Cancer Continuum” (NNACC) - Burhansstipanov, Linda (2012)
This community-based participatory research (CBPR) study was based on patient navigation (Navigator) among three original sites: Colorado, Michigan, and South Dakota. During 2010, the study added two sites: the Comanche Nation and the Muscogee (Creek) Nation (Oklahoma). The intervention includes 24-h of a Navigator-implemented cancer education program that addresses the full continuum of cancer care. The partners include agreements with up to two local Native American organizations each year, called Memorandum Native Organizations, who have strong relationships with local American Indians. Family fun events are used to initiate the series of workshops and to collect baseline data and also to wrap up and evaluate the series 3 months following the completion of the workshop series. Evaluation data are collected using an audience response system (ARS) and stored using an online evaluation program. Among the lessons learned to date are: the Institutional Review Board processes required both regional and national approvals and took more than 9 months. All of the workshop slides were missing some components and needed refinements. The specifics for the Memorandum Native Organization deliverables needed more details. The ARS required additional training sessions, but once learned the Navigator use the ARS well. Use of the NACR website for a password-protected page to store all NNACC workshop and training materials was easier to manage than use of other online storage programs. The community interest in taking part in the workshops was greater than what was anticipated. All of the Navigators’ skills are improving and all are enjoying working with the community.